Acid Based Accounting (ABA) For Acid Mine Drainage Prediction - Wu, Chuen Li (Universiti Sains Malaysia, 2022)
In these recent years, acid mine drainage becoming serious in Malaysia. For example, in Pahang, there are 3 abandoned mine site that is water bodies already acidic. This study is aimed to investigate the acid mine drainage potential and characterization of the gold mine tailing from Kelantan, Tanah Merah gold mine.The sample Vat leaching (VL) and Heap leaching (HL) tailing are analyzed for potential Acid Mine Drainage (AMD) production. The samples were inspected by visual observation, analyzed by X-ray Diffraction (XRD), X-ray Fluorescence (XRF) and Carbon Hydrogen Nitrogen sulfur analyzer (CHNS). For the static test, Acid Based Accounting (ABA) test and Net Acid Generation (NAG) with Paste Ph was done. From ABA, the result of Neutralizing Potential (NP) is obtained and subtracted with Acid Potential (AP) to get the value of Net Neutralizing Potential (NNP). The kinetic test is a batch reactor test. The finding of the project is VL, and HL samples are non-acid mine drainage production. The limitation of the project would be, for the determination of NAG, the temperature required is difficult to maintain at steady state for a long time, and in the determination of Neutralizing potential, using solely fizz rating to estimate required amount of HCl is not really satisfied. In future study regarding the gold tailing, study might can focus on doing on comparing result of the tailing samples with the different static test, to see howdifferent method gives different values, and finding on reason that the solution of HL was red yellowish.